Predictors of Unfavorable Outcomes in Patients with Atrial Fibrillation and Concomitant Heart Failure with Different Ejection Fractions: RIF-CHF Register One-Year Follow-Up. (15th May 2019) - Zhirov, Igor; Safronova, Natalia; Osmolovskaya, Yulia; Alshevskaya, Alina; Moskalev, Andrey; Tereshchenko, Sergey
Abstract : Background . Atrial fibrillation (AF) and heart failure (HF) are tightly interrelated. The concurrence of these pathologies can aggravate the pathological process. The geographic and ethnic characteristics of patients may significantly affect the efficacy of different types of therapy and patients' compliance. The objective of this study was to analyze how the features of the course of the diseases and management of HF + AF influence the clinical outcomes. Methods . The data of 1, 003 patients from the first Russian register of patients with chronic heart failure and atrial fibrillation (RIF-CHF) were analyzed. The endpoints included hospitalization due to HF worsening, mortality, thromboembolic events, and hemorrhage. Predictors of unfavorable outcomes were analyzed separately for patients with HF and preserved ejection fraction (AF + HFpEF), midrange ejection fraction (AF + HFmrEF), and reduced ejection fraction (AF + HFrEF). Prevalence of HF + AF and compliance with long-term treatment of this pathology during one year were evaluated for each patient. Results . The study involved 39% AF + HFpEF patients, 15% AF + HFmrEF patients, and 46% AF + HFrEF patients. AF + HFpEF patients were significantly older than patients in two other groups (40.6% of patients were older than ≥75 years vs. 24.8%, respectively, p < 0.001 ) and had the lowest rate of prior myocardial infarctions (25.3% vs. 46.1%, p < 0.001 ) and the lowest adherence to rational therapy of HF (27.4% vs. 47.1%, p < 0.001 ). AF + HFmrEF patients had the highest percentage of cases of HF onset after AF (61.3% vs. 49.2% in other patient groups, p = 0.021 ). Among patients with AF + HFrEF, there was the highest percentage of males (74.2% vs. 41% in other patient groups, p < 0.001 ) and the highest percentage of ever-smokers (51.9% vs. 29.4% in other patient groups, p < 0.001 ). A total of 57.2% of patients were rehospitalized for decompensation of chronic heart failure within one year; the risk was the highest for AF + HFmrEF patients (66%, p = 0.017 ). Reduced ejection fraction was associated with the increased risk of cardiovascular mortality (15.5% vs. 5.4% in other patient groups, p < 0.001 ) rather than ischemic stroke (2.4% vs. 3%, p = 0.776 ). Patients with AF + HFpEF had lower risk to achieve the combination point (stroke + IM + CV death) as compared to patients with AF + HFmrEF and AF + HFrEF (12.7% vs. 22% and 25.5%, p < 0.001 ). Regression logistic analysis revealed that factors such as demographic characteristics, disease severity, and administered treatment had different effects on the risk of unfavorable outcomes depending on ejection fraction group. The clinical features and symptoms were found to be significant risk factors of cardiovascular mortality in AF + HFmrEF, while therapy characteristics were not associated with it. Conclusions . Each group of patients with different ejection fractions is characterized by its own pattern of factors associated with the development of unfavorable outcomes. The demographic and clinical characteristics of patients with midrange ejection fraction demonstrate that these patients need to be studied as a separate cohort.